Targeting mitochondrial tyrosyl-tRNA synthetase YARS2 suppresses colorectal cancer progression. Issue 1 (31st December 2022) - Fang, Qingxia; Lin, Jingyang; Gao, Liang; Pan, Ruolang; Zheng, Xiaochun
ABSTRACT: Defects in tRNA expressions and modifications had been linked to various types of tumorigenesis and progression in recent studies, including colorectal cancer. In the present study, we evaluated transcript levels of mitochondrial tyrosyl-tRNA synthetase YARS2 in both colorectal cancer tissues and normal colorectal tissues using qRT-PCR. The results revealed that the mRNA expression level of YARS2 in colorectal cancer tissues was significantly higher than those in normal intestinal tissues. Knockdown of YARS2 in human colon cancer cell-line SW620 leads to significant inhibition of cell proliferation and migration. The steady-state level of tRNATyr, OCR, and ATP synthesis were decreased in the YARS2 knockdown cells. Moreover, our data indicated that inhibition of YARS2 is associated with increased reactive oxygen species levels which sensitize these cells to 5-FU treatment. In conclusion, our study revealed that targeting YARS2 could inhibit colorectal cancer progression. Thus, YARS2 might be a carcinogenesis candidate gene and can serve as a potential target for clinical therapy.